Cop to corpse ebook - Lovesey, Peter (Peter Diamond Mystery, 2012)
“Next to Jane Austen, Peter Lovesey is the writer the tourist board of Bath, England, extols most proudly . . . The enduring draw of the Peter Diamond books derives both from the beguiling Bath cityscape and the brusque character of Diamond himself.”  —NPR PC Harry Trasker is the third policeman in the Bath area to be shot dead in less than twelve weeks. The assassinations are the work of a sniper who seems to be everywhere and nowhere at once, always a step ahead.The younger detectives od their best with what little evidence he leaves, but they're no match for this murderer and his merciless agenda.  When Chief Superintendent Peter Diamond is assigned to the case, he begins to find curious connections between the dead officers after talking to their widows. But then a chilling encounter with the killer leaves Diamond in the lurch and the sniper in the wind. Things get even more complicated when the evidence starts to suggest that the killer might be one of Britain's finest—a theory unpopular among Diamond's colleagues. Can Diamond manage to capture an elusive and increasingly dangerous killer while keeping his team from losing faith in him?